Perceived stress and smoking across 41 countries: A global perspective across Europe, Africa, Asia and the Americas - Stubbs, Brendon; Veronese, Nicola; Vancampfort, Davy; Prina, A. Mathew; Lin, Pao-Yen; Tseng, Ping-Tao; Evangelou, Evangelos; Solmi, Marco; Kohler, Cristiano; Carvalho, André F.; Koyanagi, Ai (Scientific reports, 2017)
Within recent years, there has been a seismic shift in smoking rates from high-income to low- and middle-income countries (LMICs). Evidence indicates that perceived stress may comprise a barrier for smoking cessation, but little is known about the association of perceived stress and smoking in LMICs. We conducted a cross-sectional, community-based study comprising 217,561 people [mean age 38.5 (SD = 16.1) years, 49.4% males]. A perceived stress score [range 2 (lowest-stress) 10 (highest-stress)] was computed from the Perceived Stress Scale. Multivariable logistic regression analyses were conducted. In the overall sample, a one-unit increase in perceived-stress resulted in a 5% increased odds of smoking (OR = 1.05; 95%CI = 1.03–1.06). Increased stress was associated with smoking in Africa (OR = 1.06; 95%CI = 1.04–1.09), Americas (OR = 1.03; 95%CI = 1.01–1.05), and Asia (OR = 1.06; 95%CI = 1.04–1.08), but not Europe (OR = 0.99; 95%CI = 0.95–1.02). Increasing levels of perceived stress were significantly associated with heavy smoking (≥30 cigarettes per day) among daily smokers (OR = 1.08; 95%CI = 1.02–1.15). A country-wide meta-analysis showed that perceived stress is associated with daily smoking in most countries. Prospective studies are warranted to confirm/refute this relationship, which may have meaningful public health implications.